Challenging the surgical norm-medical management of cesarean scar ectopic pregnancy: a case report - Kanal, Preeti; Samaiya, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cesarean scar pregnancy (CSP) is a rare form of ectopic pregnancy in which implantation occurs within the myometrial defect of a previous cesarean section scar. Its incidence is rising in parallel with increasing cesarean delivery rates. Although surgical management is traditionally preferred to prevent complications such as uterine rupture and morbidly adherent placenta, selected cases may be effectively managed medically. We report the successful medical management of a 34-year-old G3P2L1 woman with two prior cesarean deliveries who presented with mild abdominal discomfort and bleeding per vaginum after a 14-day delayed menstrual cycle. Her serum β-hCG was >15,000 mIU/mL. Transvaginal ultrasonography revealed a gestational sac measuring ~11.6 mm located within the anterior myometrium at the previous cesarean scar, containing a yolk sac and fetal pole with cardiac activity, consistent with a live CSP. The patient wanted uterine-preserving medical management. This case demonstrates that even a live CSP can be successfully managed using a combined local-systemic medical approach, preserving menstrual function, uterine integrity and fertility. With cesarean rates rising globally, evidence supporting safe, effective, non-surgical alternatives is increasingly important. The patient was followed up with β-hCG levels.